Challenges and opportunities of producing participatory art in Singapore: a case study of the preproduction for unseen art initiative’s ‘Edible Art Club’ - Ho, Philip Zhi Yang (Nanyang Technological University, 2024)
This paper examines participatory art and its growing popularity in contemporary art practices in the Singaporean art scene. It focuses specifically on the relationship between local creatives and State (and State-affiliated) funders, which has remained as one of the most significant determining factors in the development of the socio-political potential of the arts locally.